Coordinating ecological risk assessment with natural resource damage assessment: A panel discussion. (17th February 2016) - Sanders, Brenda; Ammann, Mike; Hoff, Rebecca; Huston, Mark; Jenkins, Kenneth; Palagyi, Tony; Pelto, Karen; Rettig, Todd; Wagner, Anne
ABSTRACT: Contaminated sites in the United States undergo remediation and restoration through regulatory programs that lead the 2 processes through independent but often parallel pathways with different objectives. The objective of remediation is to reduce risk to human health and the environment, whereas that of restoration is to restore injured resources and compensate the public for lost use of the services that natural resources provide. More complex sites, such as those associated with large river systems and urban waterways, have resulted in increasingly larger‐scale ecological risk assessments (ERAs) and natural resource damage assessments (NRDAs) that take many years and involve diverse practitioners including scientists, economists, and engineers. Substantial levels of effort are now frequently required, creating a need for more efficient and cost‐effective approaches to data collection, analyses, and assessments. Because there are commonalities in the data needs between ERAs and NRDAs, coordination of the design and implementation of site‐specific studies that meet the needs of both programs could result in increased efficiency and lower costs. The Association for Environmental Health and Sciences Foundation convened a panel of environmental practitioners from industry, consulting, and regulatory bodies to examine the benefits and challenges associated with coordinating ERA and NRDA activities in the context of a broad range of regulatory programs. This brief communication presents the opinions and conclusions of the panelists on these issues and reports 2 case studies for which coordinated ERA and NRDA activities produced a positive outcome. Integr Environ Assess Manag 2016;12:616–621. © 2015 SETAC Key Points: Ecological risk assessment and natural resource damage assessment share common data needs that, if coordinated, can be structured to reduce both effort and cost relative to sites where the 2 assessments are conducted independently. To facilitate such coordination, the parties must work closely together to identify up front what data will be needed and how the data will be used for each assessment. When all parties are committed to coordinating remedial and restoration activities, both processes benefit from sharing data, resources, and knowledge to better understand the history and current conditions at the site. Further coordination can facilitate agreement regarding the bounds of uncertainty, which enables the groups to redirect their attention to restoration planning and can open up opportunities that were not previously apparent.